Database integration approaches for heterogeneous biological data sources : an overview - Ishak, Iskandar (2006)
Biological data sources are known for its heterogeneous in many aspects. These aspects include data formats, physical location as well as its query capabilities. These data sources need to be integrated so that researchers can easily access it, query it and get results. Approaches like link-driven, data warehousing and mediatorbased are being used to integrate these data sources. This paper tries to look at the dissimilarities of major biological data sources and some major approaches in dealing with the biological multi-database integration. Mediator based with ontologies approach is also discussed in this paper. Proposed work on merging biology ontologies in a mediated system is also presented.